2021
DOI: 10.19044/esj.2021.v17n35p130
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to the New Normal in Education: A Case Study of Chinese School Leaders in the Philippines

Abstract: This paper focuses on exploring the different changing roles and leadership practices of the two Chinese private school leaders in basic education in the new normal with its challenges and opportunities. This case study approach was done through semi-structured interviews and supplemented with documents including e-mails, written reports, meeting notes, and other related documents used for triangulation to strengthen the credibility of outcomes. It also enables different interpretations and meanings to be incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The researchers are the main instrument in conducting qualitative research (Pecson & Pogoy, 2021). In this meta-synthesis, the experiences of the teachers in utilizing flipped classroom were synthesized which were published in selected research articles.…”
Section: Instrumentmentioning
confidence: 99%
“…The researchers are the main instrument in conducting qualitative research (Pecson & Pogoy, 2021). In this meta-synthesis, the experiences of the teachers in utilizing flipped classroom were synthesized which were published in selected research articles.…”
Section: Instrumentmentioning
confidence: 99%
“…Discussing about preparation, Pecson and Pogoy (2021), studied about how Chinese Private School Leaders in the Philippines lead their school in the context of during and, in anticipation, after the pandemic. Their research found that these Chinese school leaders practice Situational Leadership, Edukasiana: Jurnal Inovasi Pendidikan, 3(2), 2024, pp.…”
Section: Introductionmentioning
confidence: 99%
“…School leaders also tapped on their social networks in order to identify social models, and look for good examples for better practice. Lastly, school leaders in Chinese private schools made sure to share the roles and responsibilities to other employees of their school to achieve efficiency in their work (Pecson & Pogoy, 2021).…”
Section: Introductionmentioning
confidence: 99%